Optimizing nitrogen management for young rubber trees: gradients effects on nutrient partitioning and root structural adaptation - Zhang, Yongfa; Jin, Dongqi; Luo, Xuehua; Zhao, Chunmei; Xue, Xinxin; Ren, Changqi; Wu, Xiaoshuang; Wang, Yu; Zhang, Jingmin; Luo, Wei; Wang, Wenbin (Frontiers in Plant Science, 2025)
IntroductionEfficient nitrogen (N) management is crucial for the sustainable cultivation of rubber tree (Hevea brasiliensis) seedlings.MethodsThis study aimed to determine the effects of low (CK, 32.4 g tree⁻¹), medium (MN, 64.8 g tree⁻¹), and high (HN, 97.2 g tree⁻¹) nitrogen application on plant growth, chlorophyll content, nitrogen allocation, and root architecture in young rubber trees.ResultsResults indicate that MN application optimized plant performance. The MN treatment yielded the highest sustained chlorophyll a+b content, peaking 60 days post-fertilization, and the lowest chlorophyll a/b ratio. It also demonstrated superior nitrogen fertilizer utilization, with significantly higher nitrogen derived from fertilizer (Ndff) in leaves across various growth stages and in most organs during dormancy. Consistently, MN application resulted in the highest whole-plant biomass (846.88 g/plant) and total nitrogen accumulation (13.79 g/plant), with a marked increase in allocation to structural components. The MN treatment promoted the development of a more vigorous fine root system during dormancy, with significantly greater root length, diameter, surface area, and volume. Correlation analysis revealed significant positive associations between fine root N content/Ndff and these root architectural traits.DiscussionConsequently, while HN application provides a transient boost in chlorophyll a, it is associated with lower nitrogen uptake efficiency and increased dependence on soil nitrogen, leading to reduced biomass and N accumulation. This pattern of inefficiency under high nitrogen inputs underscores suboptimal fertilizer use and suggests a greater potential for environmental nitrogen losses. Therefore, medium nitrogen application emerges as the most effective strategy for enhancing seedling growth and nitrogen use efficiency in young rubber tree seedlings.